2001
DOI: 10.1105/tpc.010168
|View full text |Cite
|
Sign up to set email alerts
|

A Gene Related to Yeast HOS2 Histone Deacetylase Affects Extracellular Depolymerase Expression and Virulence in a Plant Pathogenic Fungus

Abstract: A gene, HDC1 , related to the Saccharomyces cerevisiae histone deacetylase (HDAC) gene HOS2 , was isolated from the filamentous fungus Cochliobolus carbonum , a pathogen of maize that makes the HDAC inhibitor HC-toxin. Engineered mutants of HDC1 had smaller and less septate conidia and exhibited an ‫ف‬ 50% reduction in total HDAC activity. Mutants were strongly reduced in virulence as a result of reduced penetration efficiency. Growth of hdc1 mutants in vitro was normal on glucose, slightly decreased on sucros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…For Cochliobolus carbonum , a plant pathogenic ascomycete, it has been shown that the HOS2‐related histone deacetylase HDC1 is required for the expression of various glucose‐repressed extracellular enzymes that can depolymerize the plant cell wall. As a consequence, hdc1 mutants are non‐pathogenic (Baidyaroy et al. , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For Cochliobolus carbonum , a plant pathogenic ascomycete, it has been shown that the HOS2‐related histone deacetylase HDC1 is required for the expression of various glucose‐repressed extracellular enzymes that can depolymerize the plant cell wall. As a consequence, hdc1 mutants are non‐pathogenic (Baidyaroy et al. , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Classical HDACs and their interacting partners have been characterized for roles in plant pathogenicity in a few pathosystems. In the maize pathogen Cochliobolus carbonum , the class II HDAC‐encoding orthologue of yeast HOS2 , HDC1 , was found to be required for virulence (Baidyaroy et al ., ). In Fusarium graminearum , the cause of head blight in wheat and barley, the HOS2 orthologue HDF1 was required for virulence on wheat heads and corn stalks (Li et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Hos2 orthologs also exist in filamentous fungi (Brosch, Loidl, & Graessle, ), such as HosA in Aspergillus nidulans (Graessle et al, ) or HDC1 required for extracellular depolymerase expression and virulence in Cochliobolus carbonum (Baidyaroy et al, ). Hos2 has been shown to act as a key component of the Tig1 complex essential for infectious growth and conidiogenesis in Magnaprothe oryzae (Ding et al, ), mediate sexual/asexual development and pathogenesis in Fusarium graminearum (Li et al, ), and act as a downstream component of the cAMP‐PKA pathway and a transcriptional regulator of the mating‐type genes required for dimorphic switch and pathogenesis in Ustilago maydis (Elías‐Villalobos, Fernández‐Álvarez, Moreno‐Sánchez, Helmlinger, & Ibeas, ).…”
Section: Introductionmentioning
confidence: 99%